2014
DOI: 10.1159/000357639
|View full text |Cite
|
Sign up to set email alerts
|

Low Hip Bone Mineral Density Predicts Mortality in Maintenance Hemodialysis Patients: A Five-Year Follow-Up Study

Abstract: Background: Bone loss is common among hemodialysis patients and contributes to mortality. The association between bone loss and vascular calcification may explain the increased mortality risk. Studies on the association between decreased bone mass and mortality in maintenance hemodialysis patients are limited. Methods: Eighty-three hemodialysis patients underwent bone mineral density (BMD) and coronary artery calcification (CAC) measurements. The relationship between BMD and mortality was analyzed after a 5-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
3
14
0
Order By: Relevance
“…No differences were found in BMD between hemodialysis and peritoneal dialysis [17]. Low BMD also represents an independent mortality risk factor [18].…”
Section: Introductionmentioning
confidence: 90%
“…No differences were found in BMD between hemodialysis and peritoneal dialysis [17]. Low BMD also represents an independent mortality risk factor [18].…”
Section: Introductionmentioning
confidence: 90%
“…Comparing to general population of the same age, the severity of atherosclerosis and vascular calcification in CKD patients is intensified by the prolonged exposure to phosphate retention, the increased calcium load from calcium based phosphate binder and high dialysate calcium and the presence of uremia and inflammation [51,52] . The prevalence of coronary artery calcification (CAC) in dialysis patients ranges between 80%90% [53,54] . In a study that evaluated vascular calcification at the time of transplantation found the presence of CAC in 65% [55] .…”
Section: Vascular Calcificationmentioning
confidence: 99%
“…Evaluation of the effects of ELF-PEMF in our patients did not have the aim to investigate the effects on osteoporosis because, as mentioned above, the role and usefulness of DXA in assessing bone status is not well defined. But it was demonstrated that patients with ESRD and low BMD have a significantly shorter survival and that reduced BMD is also predictive of increased allcause mortality and cardiovascular mortality [14][15][16][17] . According to the eldest cross-sectional study of von der Recke et al 17 , low hip BMD seems to predict all-cause mortality in ESRD patients after adjustment for age, years of menopause, presence of hypertension, smoking, and abnormalities in the lipid profile.…”
Section: Discussionmentioning
confidence: 99%